Between the lights [videorecording (DVD)] - Groom, Michael (Film director); Groom, David (Film producer) (Freestyle Digital Media, 2025)
Skeptical scientist Alice falls for reluctant medium Jay in an odyssey of love, loss and discovery that will turn her world upside down.